Synthesis of Bifacial Peptide Nucleic Acids with Diketopiperazine Backbones - Devari, Shekaraiah; Bhunia, Debmalya; Bong, Dennis (Synlett, 2022)
We report a synthesis of bifacial peptide nucleic acids (bPNAs) with novel diketopiperazine (DKP) backbones that display unnatural melamine (M) bases, as well as native bases. To examine the structure–function scope of DKP bPNAs, we synthesized a set of bPNAs by using diaminopropionic acid, diaminobutyric acid, ornithine, and lysine derivatives to display the base-tripling motifs, which result in one, two, three, or four carbons linking the alpha carbon to the side-chain amine. Thermal denaturation of DNA hybrids with these bPNAs revealed that the optimal side-chain linkage was four carbons, corresponding to the lysine derivative. Accordingly, monomers displaying two bases per side-chain were prepared through double reductive alkylation of the ε-amine of Fmoc-lysine with acetaldehyde derivatives of adenine, cytidine, uridine, and melamine. With these building blocks in hand, DKP bPNAs were prepared to display a combination of native and synthetic (melamine) bases. Preliminary melting studies indicate binding signatures of cytidine- and melamine-displaying bPNAs to T-rich DNAs of noncanonical structure, though full characterization of this behavior is ongoing. The convenient and potentially scalable method described enables rapid access to DNA-binding scaffolds of low (<1 kD) molecular weight and previously established cell permeability. We expect that this straightforward and efficient approach to nucleic acid binders will enable studies on noncanonical nucleic acid hybridization.
Keywords: peptide nucleic acids; diketopiperazines; DNA binding; triplexes